2015
DOI: 10.1007/s00595-015-1164-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive esophagectomy performed with the patient in a prone position: a systematic review

Abstract: Theoretically, the operative results of MIE-PP might be better than those of MIE-LP for patients with esophageal cancer; however, studies have not yet verified this. Further clinical studies are required to establish whether the advantages of MIE-PP can be translated into clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 76 publications
0
19
0
4
Order By: Relevance
“…Rino et al (2014) reported that the use of absorbable dense knit hemostat, instead of an electrocautery device, for hemostasis around the RLN could prevent the RLNP during esophageal cancer surgery. Thoracoscopic esophagectomy has been employed as minimally invasive surgery (Saikawa et al 2014;Koyanagi et al 2015). Although magnification of the surgical fields can enable a precise lymph node dissection along the RLN, the advantages of a thoracoscopic esophagectomy for reducing the RLNP continues to be debated.…”
Section: Discussionmentioning
confidence: 99%
“…Rino et al (2014) reported that the use of absorbable dense knit hemostat, instead of an electrocautery device, for hemostasis around the RLN could prevent the RLNP during esophageal cancer surgery. Thoracoscopic esophagectomy has been employed as minimally invasive surgery (Saikawa et al 2014;Koyanagi et al 2015). Although magnification of the surgical fields can enable a precise lymph node dissection along the RLN, the advantages of a thoracoscopic esophagectomy for reducing the RLNP continues to be debated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from Japan have shown the benefits of MIE in the prone position in terms of better surgical exposure, a larger number of dissected lymph nodes and less blood loss compared to MIE in the left lateral decubitus position. However, most cases undergo MIE in the left lateral decubitus or semi‐prone position in China .…”
Section: Discussionmentioning
confidence: 99%
“…Esophagectomy with radical lymphadenectomy plays the most vital role in treating patients with esophageal cancer. With the development of endoscopic equipment and the progress of surgical technology, minimally invasive esophagectomy (MIE), which is characterized by minimal access, lower postoperative pain, fewer complications and fast recovery, has become the treatment of choice in recent years …”
Section: Introductionmentioning
confidence: 99%
“…Geralmente, os divertículos de tração não apresentam sintomas, porém dependendo do tamanho do divertículo e do estágio da doença é comum o aparecimento de disfagia, regurgitação, mau hálito, rouquidão ou pneumopatias (5) . Aspiração, tosse e complicações, como a infecção, a perfuração e a transformação neoplásica, são razões pelas quais o tratamento cirúrgico é recomendado (6) .…”
Section: Introductionunclassified